BIOLOGICAL DESULFURIZATION OF THE BIOGAS IN ENVIRONMENTAL CONDITIONS OF BRAZIL - Müller, R.; Feiden, A.; Marques, F.S.; Lucio, L.T.; Mari, A.G. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Processes for biogas production are fine resolved commercially in Brazil. However, biogas is not robust to the point of being understood by agroindustry as a product, which can generate electrical, thermal or vehicular energy, because its purification process still lacks technology for low cost, especially for small and medium sized agroindustries. The objective of this study is to evaluate the use of biological desulfurization process in Brazil.